2021
DOI: 10.5267/j.ijdns.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Human resources practices and job satisfaction on customer satisfaction: The mediating role of quality of customer interaction in online call center

Abstract: The frequently discussed topic of job satisfaction is not new in the field of organizational behavior research. Job satisfaction is related to customer satisfaction; however, there is a scarcity of empirical evidence regarding this link. The current piece of research examines the said relationship in the context of the online call center. In addition, this study investigates the effect of human resources (HR) practices on job satisfaction within the online call center context. The sample of the study consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 1 publication
2
18
0
3
Order By: Relevance
“…Because the satisfaction of employee makes them more committed to their work and customers (Amoopour et al, 2014). Eneizan et al (2021) confirmed the positive effect of job satisfaction on customer satisfaction. A satisfied employee is key to accomplish organizational goals.…”
Section: Job Satisfaction and Customer Satisfactionmentioning
confidence: 79%
See 2 more Smart Citations
“…Because the satisfaction of employee makes them more committed to their work and customers (Amoopour et al, 2014). Eneizan et al (2021) confirmed the positive effect of job satisfaction on customer satisfaction. A satisfied employee is key to accomplish organizational goals.…”
Section: Job Satisfaction and Customer Satisfactionmentioning
confidence: 79%
“…The items of Job Satisfaction were adopted from Al-dalahmeh et al (2018), Hanaysha and Tahir (2016). The items of customer satisfaction were adopted from Bamberger et al (2021), Eneizan et al (2021). The items of firm performance were adopted from Al-dalahmeh et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telecommunication company should pay greater attention to the findings of this study and build appropriate programs aimed at increasing the satisfaction level of its employees because they are the ones who are working with the customers, and if employees are dissatisfied, it may directly or indirectly result in the customer dissatisfaction through bad service quality provided by the employees (Kurdi et al. , 2020; Eneizan et al. , 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies indicate that the application of human resource management practices in educational organizations such as universities and public and private institutes brings many positive results such as improving employees' performance which reflects on the organizational performance in terms of employees' performance levels and thus the organizational performance levels in general (Eneizan et al, 2021;Alsakarneh, 2019;Saifalislam et al, 2014;Amin et al, 2014). Studies have also indicated that the application of human resource management practices in universities helps improve the university rank (Ashraf et al, 2014), retain senior employees (Kosi et al, 2015;Hong et al, 2012), and raise job satisfaction levels among faculty members (Mumtaz et.…”
Section: Commitment To the Relevant Government Legislationsmentioning
confidence: 99%